G111(P) Have we hit the mark? Boosting confidence to improve outcomes in stressful situations. (25th October 2020) - Rehman, L; Kamal, M; Cahill, P; Hussain, M; Shahid, M
Abstract : Aim: To analyse whether initial consultant–led simulation–based–teaching–sessions (SBTS) boost junior doctors participation levels' as team leaders. To determine the influence of SBTS on non–clinical hospital doctors (NCHDs) baseline knowledge, confidence, comfort levels and situational awareness in stressful Paediatric/Neonatal situations. Method: A two-part survey was designed and distributed at the start of the rotation in a formal setting of 'SAFE' (Situational Awareness For Everyone) by lead consultant. 1 The first part included a comprehensive questionnaire outlining Paediatric BLS, ALS and Neonatal resuscitation to assess the baseline knowledge of all NCHDs. The second part helped us establish NCHDs experience, confidence and comfort levels when participating in SBTS sessions. 1 2 Initial three months: Neonatal and Paediatric team leaders were designated among consultants to plan/coordinate among all NCHDs. A schedule of weekly Paediatric/Neonatal scenarios was distributed. Second three months: Team members volunteered to lead random scenarios per week. Overtime, situational awareness of team members was also assessed. 1 After six months, the same survey was redistributed. Results: NCHDS' were categorised according to their level of experience in Paediatrics. NCHDs' who had between 0–1 years' experience in Paediatrics were not very confident and not very comfortable as team leaders and scored on average 63% on the baseline knowledge questionnaire. Post intervention most NCHDs had become very confident and very comfortable dealing with stressful situations and better retained baseline knowledge, scoring an average of 92%. NCHD's who had 3+ years' experience were confident and comfortable to begin with and those levels only improved over six months. 1 2 Baseline knowledge was maintained, further refining from 81 – 96%. Conclusion: Our main cohort of junior doctors is GP trainees who rotate from different specialities every six months with none - minimal Paediatric/Neonatal exposure and knowledge as evident from the above results. Initially they were reluctant to participate due to the fear of being judged. However, our consultant-led strategy boosted their knowledge, confidence and comfort levels as well as situational awareness to lead and deliver better patient care in stressful situations. References: Rakshasbhuvankar, Abhijeet & Patole, Sanjay. ( 2014). Benefits of simulation based training for neonatal resuscitation education: A systematic review. Resuscitation . 85. 10.1016/j.resuscitation.2014.07.005. Schweich PJ, DeAngelis C, Duggan AK. Preparedness of practicing pediatricians to manage emergencies. Pediatrics 1991;88:223.